Look Behind You! Playing with Sexual Surveillance in You Must Be 18 or Older to Enter and how do you Do It? - Ketterling, Jean (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2024)
In this article, I consider two indie videogames, You Must Be 18 or Older to Enter (Seemingly Pointless 2017) and how do you Do It? (Freeman et al. 2014), that share an interest in the affective impact of parental surveillance and discipline on childhood sexual exploration. Using close playing as my method, I argue that the videogames reveal the perils of surveillance and its pleasures. Drawing on assemblage theory, I demonstrate the contingency of videogames’ affective impact on players and the world and the—sometimes contradictory—potentials that surveillance produces as part of a sexual assemblage. Sometimes, using surveillance as a game mechanic amplifies sexual affect and pleasure and can thus be conceptualized as an example of “flirting” with surveillance. At other times, players orient themselves toward the videogames as the archetypical “parent”—finding pleasure in “catching” a videogame about sexual exploration and attempting to discipline it. Finally, drawing on Kathryn Bond Stockton (2004, 2009, 2017) and José Esteban Muñoz (2019), I argue that, by allowing players to relive childhood sexual exploration as adults, You Must Be 18 or Older to Enter and how do you Do It? provide players with the opportunity to become a playful child, to loop back through time and re-explore sexual discovery, and thus shape nuanced critiques of the way surveillance shapes sexual possibilities.